Evaluation study of the IFPRI/A4NH research program on diet quality and health of the poor: Synopsis - Behrman, Jere R.; Ghosh, Shibani (International Food Policy Research Institute, 2019)
IFPRI’s Poverty, Health, and Nutrition Division (PHND) and the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) have conducted research since 2003 on the critical links between nutrition, health, and agriculture. This evaluation considers the impact of the work carried out through 2016, looking at the research strategy, engagement, capacity building, and impact on programs and policies and global dialogue. Findings suggest that the Diet Quality and Health of the Poor program has been successful in developing and sharing valuable research, knowledge, and data, and has brought new issues and approaches to partners and stakeholders. Through a range of projects, the program has effectively engaged with stakeholders, partners, and governments to support capacity enhancement and to help shape national interventions to improve nutrition. However, the original aspirations of the program have not been fully met and challenges in terms of communication and coordination indicate there is room for improvement.